Psychosocial Education “Emotional Freedom Techniques (Eft)” for Pregnant Mothers in the Adaptation of New Habits Covid 19 - Ganda Agustina Hartati Simbolon; Marni Siregar; Sulastry Pakpahan (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2022)
ABSTRACT This community service is carried out of psychological education by providing Emotional Freedom Technique (EFT) therapy for pregnant women during the COVID-19 pandemic. This community service was conducted 3 times at the Public Health Center in Sipoholon District, namely the Situmeang Habinsaran (24 August 2021), and the Sitada-Tada (26 August 2021 and 2 September 2021), targeting 40 pregnant women in the third trimester. Depression, anxiety, and stress are three disorders that are often found in psichological disorders of pregnant women, especially during the Covid 19 pandemic. EFT is one way to reduce psychological disorders in mothers which are carried out in four set up, tapping, 9 gamut procedures, and repetition. After carrying out EFT, there was a change in the psychological response of mothers who experienced mild, moderate, and severe depression, turning into a normal state (100%). Pregnant women with anxiety disorders, experiencing changes, mild anxiety 3 people, and the remaining 33 people are in the normal category. psychological changes occur with stress disorders, namely the category of very heavy stress becomes non-existent, moderate stress 1 person, mild stress 1 person, and the rest (38 people) in normal conditions. During the adaptation period of the Covid 19 pandemic, health workers, pregnant women should continue to pay attention to preventing the transmission of Covid 19 following the health protocol. Doing EFT regularly at home will keep the body in balance, reduce stress levels, help calm the mind and body by eliminating emotional stress, and anxiety. Keywords: Education, EFT, Pregnancy, Psychological